Becker's world of the cell - Hardin, Jeff; Hardin, Jeff; Bertoni, Gregory; Kleinsmith Lewis J. (USA, Pearson, 2012)
Widely praised for its strong biochemistry coverage, Becker$1 (Bs World of the Cell, Eighth Edition, provides a clear, up-to-date introduction to cell biology concepts, processes, and applications. Informed by many years of teaching the introductory cell biology course, the authors have added new emphasis on modern genetic/genomic/proteomic approaches to cell biology while using clear language to ensure that students comprehend the material. Becker$1 (Bs World of the Cell provides accessible and authoritative descriptions of all major principles, as well as unique scientific insights into visualization and applications of cell biology.s
Include bibliographical references; Appendix A1-A27p.; Glossary G1-G26p.; Index I1-I28p.
Keywords: Cell; Cytoskeletal systems; Enzymes; Macromolecules; Botany